Study of the parameters of binding of R 61837 to human rhinovirus 9 and immunobiochemical evidence of capsid-stabilizing activity of the compound. - Moeremans, M (1992)
The binding of the antiviral compound R 61837 to human rhinovirus 9 (HRV 9) was studied quantitatively and compared with binding of R 61837 to HRV 9H, a semiresistant variant. For both strains, radiolabelled R 61387 bound to native particles only. The Kd values obtained by Scatchard analysis of saturation binding data were 37 nM for HRV 9 and 172 nM for HRV 9H, whereas the concentrations resulting in a 50% reduction of cytopathic effect were 42 nM and 840 nM, respectively. Reversibility experiments showed that 65% of the compound could be extracted with chloroform from HRV 9H but less than 5% could be extracted from HRV 9. Dissociation studies demonstrated that in the presence of excess unlabelled compound, the half-lives of the virus compound complex HRV 9 and HRV 9H were 385 and 15 min, respectively. The effect of this antirhinoviral compound on the formation of subviral particles induced by low pH or heat was also investigated. Rate zonal centrifugation experiments using [35S]methionine-labelled HRV 9 showed that binding of R 61837 protected the virus against heat (56 degrees C) and acid (pH 5.0) and that at the same concentration of R 61837 the semiresistant strain was stabilized to a lesser extent. This observation was confirmed immunochemically with nonneutralizing and neutralizing monoclonal antibodies. Both 80S and 130S subviral particles have C antigenic determinants, whereas native particles (150S) have been designated D. R 61837 prevented the switch from D to C antigenicity which can be induced by exposure of rhinoviruses to mild denaturing conditions. These findings indicate that the compound is able to prevent a conformational change of the capsid which may be a prerequisite for infection.